HIP Arthroscopy for the Treatment of Femoroacetabular Impingement: A Comparative Study between the Classic and the Outside-in Access. Issue 3 (16th May 2016) - Sandoval, Enrique; Martín-Ríos, María Dolores; Cimas, David; Masegosa, Alberto; Calvo, Emilio
Purpose: To compare the functional outcomes of patients undergoing arthroscopic surgery for the treatment of femoroacetabular impingement (FAI) performed with either the classic or the outside-in access to the hip. Methods: Data regarding patients arthroscopically treated for FAI from January 2009 to June 2013 were retrospectively reviewed and compared regarding the type of access. Results: 101 hips (91 patients) with a minimum of 12 months follow-up (mean 22 months, range 12-40 months) were included. Classic access was used in 48 cases while outside-in access was performed in 53 cases. Mean age was 37 years (range 15.7-59.6 years). Both groups were comparable with respect to preoperative characteristics. Mean operating time was 162 minutes for the outside-in group and 172 minutes for the classic access group. Complications between both groups showed no statistically significant differences but for the presence of heterotopic calcifications, which was more frequently observed regarding the outside-in access. Outcomes measured by the modified Harris Hip Score showed no overall differences regarding both types of access, except for patients under 35 years old, where there was a statistically significant increase in excellent and good outcomes with the use of the classic access in comparison to the outside-in technique. Postoperative hip motion was also significantly higher in the classic access group. Conclusions: No differences have been found in outcomes regardless the access used. Classic access seems to offer a higher postoperative range of motion and lower risk of heterotopic ossifications.